Modular DNA origami–based electrochemical detection of DNA and proteins - Byoung-jin Jeon; Matteo M. Guareschi; Jaimie Marie Stewart; Emily Wu; Ashwin Gopinath; Netzahualcóyotl Arroyo-Currás; Philippe Dauphin-Ducharme; Kevin W. Plaxco; Philip S. Lukeman; Paul W. K. Rothemund (Proceedings of the National Academy of Sciences, 2025)
The diversity and heterogeneity of biomarkers has made the development of general methods for single-step quantification of analytes difficult. For individual biomarkers, electrochemical methods that detect a conformational change in an affinity binder upon analyte binding have shown promise. However, because the conformational change must operate within a nanometer-scale working distance, an entirely new sensor, with a unique conformational change, must be developed for each analyte. Here, we demonstrate a modular electrochemical biosensor, built from DNA origami, which is easily adapted to diverse molecules by merely replacing its analyte binding domains. Instead of relying on a unique nanometer-scale movement of a single redox reporter, all sensor variants rely on the same 100-nm scale conformational change, which brings dozens of reporters close enough to a gold electrode surface that a signal can be measured via square-wave voltammetry, a standard electrochemical technique. To validate our sensor’s mechanism, we used single-stranded DNA as an analyte, and optimized the number of redox reporters and various linker lengths. Adaptation of the sensor to streptavidin and Platelet-Derived Growth Factor-BB (PDGF-BB) analytes was achieved by simply adding biotin or anti-PDGF aptamers to appropriate DNA linkers. Geometrically optimized streptavidin sensors exhibited signal gain and limit of detection markedly better than comparable reagentless electrochemical sensors. After use, the same sensors could be regenerated under mild conditions: Performance was largely maintained over four cycles of DNA strand displacement and rehybridization. By leveraging the modularity of DNA nanostructures, our work provides a straightforward route to the single-step quantification of arbitrary nucleic acids and proteins.